Shrink : story of a fat girl - Thomas, Rachel M. (Graphic Mundi, 2024)
"A graphic novel examining the fat body in contemporary Western culture through the experiential journey of the book's hero, who chooses to lose weight in a world that has dictated the medical and social dangers of being too fat"--